International perspectives on outcome measurement in pulmonary rehabilitation of people with COPD: a qualitative study - Souto-Miranda, Sara (2022)
Background There is high heterogeneity of outcomes and measures reported in the literature for pulmonary rehabilitation (PR), which might limit benchmarking and an effective evidence synthesis. A core outcome set (COS) can minimise this problem. It is however unclear which outcomes and measures are most important and suitable for different stakeholders. Methods A multicentre qualitative study with one-to-one semi-structured interviews with people with chronic obstructive pulmonary disease (COPD), healthcare professionals (HCPs), researchers and policy makers was conducted. Manifest content analysis was conducted to explore the frequency of outcomes viewed as crucial or not. Thematic analysis was performed to better understand stakeholders’ views. Results 37 participants (17 people with COPD and 20 HCPs/researchers/policy makers) from 14 countries and 4 continents were included. Participants expressed that i) core outcomes need to be meaningful to people with COPD and show PR benefits; ii) there should be comprehensive assessment and similar outcomes across settings; iii) a balance between optimal and practical measures is needed; iv) the COS is needed to benchmark PR and advance knowledge; and v) reluctance to change outcomes/measures used by HCPs and using the COS as a maximum set of outcomes might be the pitfalls. 28 outcomes were identified as crucial, and 12 as not crucial. Conclusions This study provided important insights into outcome measurement in PR from the perspectives of different key international stakeholders and a list of outcomes that will inform a future consensus study.